Testing and selection of lubricant emulsions for reduction of unwanted soot marks during annealing of cold-rolled steel coils - Kukhar, V. V.; Spichak, O. Yu.; Pashynskyi, V. V.; Malii, Kh. V.; Кухар, В. В.; Спічак, О. Ю.; Пашинський, В. В.; Малій, Х. В. (SPOLOM, 2024)
The paper analyses the causes of soot-type defects after annealing coils rolled with emulsions and identifies the need to reduce these problems by establishing requirements for the physical and chemical properties of lubricating and cooling fluids. A methodology was developed for testing the tendency of emulsions to form soot after annealing in coils.
Keywords: cold rolling; emulsion; emulsol; lubricating-cooling fluid; physicochemical properties; requirements; soot; burnt; propensity for soot formation